Deprescribing anticholinergic and sedative medicines: protocol for a Feasibility Trial (DEFEAT-polypharmacy) in residential aged care facilities. Issue 4 (16th April 2017) - Ailabouni, Nagham; Mangin, Dee; Nishtala, Prasad S
Abstract : Introduction: Targeted deprescribing of anticholinergic and sedative medicines can lead to positive health outcomes in older people; as they have been associated with cognitive and physical functioning decline. This study will examine whether the proposed intervention is feasible at reducing the prescription of anticholinergic and sedative medicines in older people. Methods and analysis: The Standard Protocol Items: Recommendations for Interventional trials (SPIRIT checklist) was used to develop and report the protocol. Single group (precomparison and postcomparison) feasibility study design. Study population: 3 residential care homes have been recruited. Intervention: This will involve a New Zealand registered pharmacist using peer-reviewed deprescribing guidelines, to recommend to general practitioners (GPs), sedative and anticholinergic medicines that can be deprescribed. The cumulative use of anticholinergic and sedative medicines for each participant will be quantified, using the Drug Burden Index (DBI). Outcomes: The primary outcome will be the change in the participants' DBI total and DBI PRN 3 and 6 months after implementing the deprescribing intervention. Secondary outcomes will include the number of recommendations taken up by the GP, participants' cognitive functioning, depression, quality of life, activities of daily living and number of falls. Data collection points: Participants' demographic and clinical data will be collected at the time of enrolment, along with the DBI. Outcome measures will be collected at the time of enrolment, 3 and 6 months' postenrolment. Ethics and dissemination: Ethics approval has been granted by the Human Disability and Ethics Committee. Ethical approval number (16/NTA/61). Trial registration number: Pre-results; ACTRN12616000721404 .